Effect of Covid-19 Vaccine on Women’s Fertility Hormones - Haydar Basim Najeb; Abdulameer Jasim Mohammed; Emad Mohammed Rasheed (Journal of Techniques, 2022)
The coronavirus disease 2019 (COVID-19), as a result of the modern intense respiratory syndrome coronavirus 2, caused an unexpected fundamental global raise in the admission to hospitals for lung and other organ diseases. COVID-19 vaccination has increased and accelerated in a conscionable progress. More than 184 nominee vaccines are being tested in preclinical use and 104 in clinical stages of development. The current study aimed to know the impact of the COVID-19 vaccine on female fertility hormones. The results obtained from the current study showed a slight increase in FSH and LH hormones for women infected with Covid-19 virus and for women who received the vaccine to prevent covid-19 virus compared to healthy, uninfected and unvaccinated groups (FSH 10.26±3.86 ,15.32±2.04 LH 15.41±2.76, 10.40±1.58 respectively), with non-significant differences (P>0.05), while the prolactin hormone levels showed a highly significant increase (P<0.01) in infected women who took the vaccine in comparison with its levels in healthy women who did not receive the vaccine and not infected (32.32±6.48, 19.62±4.04, 10.27±6.88 respectively). Conclusions: Covid- 19 vaccine affected the female hormones in one way or another.